Riesgos de ciberadicción en estudiantes de una I.E del municipio de Ansermanuevo – Valle (2022)
This research focuses on how the risks of cyber addiction have gained strength in recent times, especially from early stages of development, due to the high utility and influence it has had on the community on platforms and technological media in the field of addiction. virtuality, reflecting in this research the negative impact on the stages of childhood and adolescence from their physical, cognitive, emotional and social development based on the theory of Jean Piaget and the development of the psychosocial and personal evolution of Erik Erikson.